2020
DOI: 10.3390/su12187794
|View full text |Cite
|
Sign up to set email alerts
|

Country’s Entrepreneurial Environment Predictors for Starting a New Venture—Evidence for Romania

Abstract: Entrepreneurship has been recognized as a key contributor to the economic development of countries and societal wellbeing. Building and sustaining an adequate entrepreneurial climate challenges—to a high extent—transitional economies world-wide, pushing these countries to develop policies and strategies aimed to sustain high-quality national entrepreneurship. The paper seeks to understand the key determinants of a country’s entrepreneurial environment that drive potential entrepreneurs to assume an entrepreneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…This was made possible by reporting, per county, the values each components at the sum of components, per component. I 2 , I 5 , I 6 and I 15 were attributed negative signs, because they represent the opposite of health [79] and wellbeing [55,56,[60][61][62]75,76]. Summing up the scores obtained per county and per component, the composite indicator resulted.…”
Section: Methodsmentioning
confidence: 99%
“…This was made possible by reporting, per county, the values each components at the sum of components, per component. I 2 , I 5 , I 6 and I 15 were attributed negative signs, because they represent the opposite of health [79] and wellbeing [55,56,[60][61][62]75,76]. Summing up the scores obtained per county and per component, the composite indicator resulted.…”
Section: Methodsmentioning
confidence: 99%
“…Approaching another perspective, Paunescu et al analyzed the Romanian entrepreneurial environment to understand the component of entrepreneurial intention. The authors demonstrated that, in Romania, the incentives for entrepreneurship could be offered by the technological availability and stability of the rules [54]. This demonstration, touching on the delicate subject of rule stability, provides another reason for the decline in entrepreneurial activity.…”
Section: Entrepreneurship In Romaniamentioning
confidence: 96%
“…As an alternative, the term "social venture" is sometimes used as a relative concept that can compensate for the limitations of venture companies that lack sustainability and growth and pursue profits in economic terms, which are the main purposes of corporate management [13]. Haugh [14] and Hockerts [15] explained that social ventures operate as business ventures that create social value by carrying out innovative activities to solve social problems, while Dees and Anderson [16] defined social ventures as legally profitoriented corporations, such as stock companies, that are explicitly designed to address social concerns while generating revenue.…”
Section: The Social Venture Conceptmentioning
confidence: 99%